The absorption of oral morroniside in rats: In vivo, in situ and in vitro studies - Xiong Shan; Li Jinglai; Mu Yanling; Zhang Zhenqing (Acta Pharmaceutica)
Morroniside is one of the most important iridoid glycosides from Cornus officinalis Sieb. et Zucc. In the present study, the pharmacokinetics and bioavailability studies of morroniside were conducted on Sprague-Dawley (SD) rats. A rat in situ intestinal perfusion model was used to characterize the absorption of morroniside. Caco-2 cells were used to examine the transport mechanisms of morroniside. The pharmacokinetic study of morroniside exhibited linear dose-proportional pharmacokinetic characteristics and low bioavailability (4.3 %) in SD rats. Its average Peff value for transport across the small intestinal segments changed from (3.09 ± 2.03) × 10−6 to (4.53 ± 0.94) × 10−6 cm s−1. In Caco-2 cells, the Papp values ranged from (1.61 ± 0.53) × 10−9 to (1.19 ± 0.22) × 10−7 cm s−1 for the apical to basolateral side and the Pratio values at three concentrations were all lower than 1.2. Morroniside showed poor absorption and it might not be a specific substrate of P-glycoprotein (P-gp).